2017
DOI: 10.1007/s12562-017-1086-0
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium fluoride influences calcium metabolism resulting from the suppression of osteoclasts in the scales of nibbler fish Girella punctata

Abstract: The influence of sodium fluoride (NaF) on calcium metabolism was examined in nibbler fish (marine teleosts). Two days after the administration of NaF (5 µg/g of body weight)(around 10-4 M in fish), we showed that plasma calcium levels significantly decreased in NaF-treated nibbler fish. In addition, we detected fluoride in the treated scales by scanning electron microscope with an energy-dispersive X-ray microanalysis, indicating that NaF directly affects their scales. Therefore, the influence of NaF on osteob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(44 reference statements)
1
10
0
Order By: Relevance
“…In addition, we found that ALP activity appeared to have decreased remarkably. ALP activity is also known as an osteoblastic marker [11,21,30], although ALP is a marker of liver diseases [31,32]. In the present study, we indicated that the mRNA expression of the osteoblastic marker COL1A1 decreased significantly.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…In addition, we found that ALP activity appeared to have decreased remarkably. ALP activity is also known as an osteoblastic marker [11,21,30], although ALP is a marker of liver diseases [31,32]. In the present study, we indicated that the mRNA expression of the osteoblastic marker COL1A1 decreased significantly.…”
Section: Discussionsupporting
confidence: 55%
“…The separated plasma was immediately frozen and kept at -80 • C until use. The plasma total Ca levels (mg/dL) were determined using an assay kit (Calcium E, FUJIFILM Wako Pure Chemical Corporation) as described in Suzuki et al (2017) [20] and Sato et al (2017) [21]. The plasma Pi levels (mg/dL) were measured using an assay kit (IP-II, Kyowa MEDEX Co., Ltd., Tokyo, Japan).…”
Section: Effects Of Baa On Plasma Ca and Pi Levels In Nibbler Fishmentioning
confidence: 99%
See 2 more Smart Citations
“…A TaqMan probe was used for Calcitonin (Figure ). Elongation factor 1 alpha ( Ef1α ) was used for the standardization procedure …”
Section: Methodsmentioning
confidence: 99%